Integração entre a robótica educacional e a abordagem steam: identificação da área de oportunidade e desenvolvimento de protótipos - Castelli Fernandes, Nidia Mara Melchiades (Universidade Federal de São Carlos, 2022)
It is totally necessary to introduce Digital Information and Communication Technologies (DICT) as a didactic resource in classrooms to face the challenges of Society nowadays. One of the technologies that has been used is Educational Robotics (ER) which, because of its characteristics, includes motivating didactic-pedagogical conditions and provides active learning. ER involves building, programming and manipulating robotic platforms. Its potential can be increased when associated to STEAM, based on investigative projects that starts from real problems and contextualized and interdisciplinary contents, where students propose a viable solution prototype. In this case, the following research question was established: How to identify areas of opportunity or themes that aim to integrate ER and the STEAM, in order to support the development of prototypes by students from Integrated Technical Education to High School? The identification of the areas and opportunities that can become the main theme for the study of the STEAM project, based on the competences developed in a curriculum, consisted in three stages: survey of the themes; classification of themes; achievement of Opportunity Areas (topics to be worked on the STEAM project) from Connection Maps. Were identified twelve Opportunity Areas, among which was chosen one of them, entitled Social Responsibility and Sustainability. After the selection, there was the development of the STEAM projects, by the students of a 1st grade of the Informatic to internet-Etim, course of an Etec in the interior of São Paulo State, belonging to the Paula Souza Center (CPS), containing five moments: 1st) Guiding question connected to a real problem; 2nd) Understanding the problem. What do we know about this subject? And, what do not we know? Polling; 3rd) Motivational texts and lectures for discussion and recording of ideas considered important by the groups; 4th) Product: development of a prototype as a proposal to solve the problem using the ER; 5th) Socialization and evaluation of prototypes. The analyzes indicate that there were advances in the knowledge learned by the students, as well as their intellectual (creativity, curiosity, reasoning, argumentation, decision-making, problem solving) and social (interaction, communication, collaboration and active listening) development.
Integration between educational robotics and the steam approach: identification of the area of opportunity and prototype development
Keywords: Robótica educacional; STEAM; Mapa de conexões; Sustentabilidade; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO::HARDWARE; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::TEORIA DA COMPUTACAO::COMPUTABILIDADE E MODELOS DE COMPUTACAO